2007
DOI: 10.1103/physrevlett.98.091101
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Kick from Nonspinning Black-Hole Binary Inspiral

Abstract: When unequal-mass black holes merge, the final black hole receives a kick due to the asymmetric loss of linear momentum in the gravitational radiation emitted during the merger. The magnitude of this kick has important astrophysical consequences. Recent breakthroughs in numerical relativity allow us to perform the largest parameter study undertaken to date in numerical simulations of binary black-hole inspirals. We study nonspinning black-hole binaries with mass ratios from q=M1/M2=1 to q=0.25 (eta=q/(1+q)2 fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

40
659
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 515 publications
(701 citation statements)
references
References 39 publications
40
659
2
Order By: Relevance
“…According to numerical relativity results, when two spinning black holes collide, gravitational radiation could be emitted asymmetrically. This would lead to a recoil velocity in the resulting black hole that might be as high as 4000 km s −1 (Gonzalez et al 2007;Campanelli et al 2007b,a;Healy et al 2009;Herrmann et al 2007), depending on the mass ratio of the initial black holes and the directions of their spins, but this velocity might be significantly suppressed by the relativistic alignment of the spins (Kesden et al 2010). It is not easy, of course to include numerical relativity in an N-body code, but semi-analytical formulae, coming from fitting between numerical relativity results and post-Newtonian theory (Lousto & Zlochower 2008;Baker et al 2008;Lousto et al 2010) to determine the direction and magnitude of the recoil velocity.…”
Section: Discussionmentioning
confidence: 99%
“…According to numerical relativity results, when two spinning black holes collide, gravitational radiation could be emitted asymmetrically. This would lead to a recoil velocity in the resulting black hole that might be as high as 4000 km s −1 (Gonzalez et al 2007;Campanelli et al 2007b,a;Healy et al 2009;Herrmann et al 2007), depending on the mass ratio of the initial black holes and the directions of their spins, but this velocity might be significantly suppressed by the relativistic alignment of the spins (Kesden et al 2010). It is not easy, of course to include numerical relativity in an N-body code, but semi-analytical formulae, coming from fitting between numerical relativity results and post-Newtonian theory (Lousto & Zlochower 2008;Baker et al 2008;Lousto et al 2010) to determine the direction and magnitude of the recoil velocity.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, progress in numerical relativity (NR) [6][7][8] has allowed relativists to simulate the mergers of highly spinning, comparable-mass black holes. For non-spinning binaries, ensuing studies identified a maximum recoil of 175 km/s [9]. Simulations of spinning black holes, however, resulted in one of the greatest surprises of numerical relativity; for equal-mass binaries with opposite spins in the orbital plane gravitational recoils can * berti@phy.olemiss.edu † mhk10@nyu.edu ‡ sperhake@tapir.caltech.edu approach 4,000 km/s [10,11], greater than the escape velocity of even the most massive galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…For non-spinning binaries, ensuing studies identified a maximum recoil of 175 km/s [9]. Simulations of spinning black holes, however, resulted in one of the greatest surprises of numerical relativity; for equal-mass binaries with opposite spins in the orbital plane gravitational recoils can * berti@phy.olemiss.edu † mhk10@nyu.edu ‡ sperhake@tapir.caltech.edu approach 4,000 km/s [10,11], greater than the escape velocity of even the most massive galaxies. This theoretical result seems at first difficult to reconcile with observations indicating that almost all large galaxies host SBHs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Baker et al (2008) modeled the coalescence of nonspinning BHs with different mass ratios. Also, González et al (2007) and Campanelli et al (2007) studied the cases with general spin orientations. These simulations show that for mergers with BHs of low spins or the spins aligned, the maximum speeds of the kick are below 200 km s −1 .…”
Section: Discussionmentioning
confidence: 99%